Livet i egen bolig: Ældres oplevelser af byrum - Johansen, Randi Sørensen; Jensen, Tenna (Grønlandsk Kultur- og Samfundsforskning, 2024)
Aging is one of the central issues of political welfare discussions in Kalaallit Nunaat. While the national policy supports senior adults’ remaining in their own homes for as long as possible, there are a number of challenges to be faced before this goal can be achieved. This article addresses one of these challenges, the ability of seniors to effectively navigate the urban environment in Nuuk. Based on interviews with older adults, this work focuses on seniors’ experience of the existing design of urban spaces within Nuuk and the possibilities of creating a more elder-friendly environment. Our analysis demonstrates how the current distance to urban centers and shops present challenges to the quality of life among self-sufficient older people. It also highlights how lack of public transport, footpaths, and amenities, such as benches, present obstacles to completing daily activities, like shopping and social engagements, while also generally adding to the difficultly of outdoor pursuits.